Exploring the nexus of green human resource management, leadership and organizational culture on workplace pro-environmental behavior - Huijun Gao; Abdullah Al Mamun; Mohammad Masukujjaman; Qing Yang (Humanities & Social Sciences Communications)
Abstract With the increase in awareness about climate change, preservation of natural resources, and environmental protection, organizations are facing a mounting pressure to adopt environmentally sustainable development strategies. To enact such policies, organizations are striving to encourage pro-environmental behaviors among employees and cultivate environmental management strategies through the adoption of green human resource management practices and the establishment of a green organizational culture. This study explores the connection between green human resource management practices, green organizational culture, and employees’ pro-environmental behaviors, with a special focus on the ecological management practices of Chinese manufacturing and service companies. By establishing an integrated model through ability-motivation-opportunity and social identity theories, this study examined the mechanisms by which green human resource management influences green organizational culture and employee pro-environmental behaviors. This study analyzed data from 412 questionnaires collected from manufacturing and service firms in southeastern China using the partial least squares method. The findings suggest that performance management and appraisal, employee empowerment and participation, recruitment and selection, and green transformational leadership have a positive impact on green organizational culture, which further positively motivates employees’ green values. Green organizational culture, green transformational leadership, and employees’ green values all have a significant impact on employees’ pro-environmental behaviors. This study provides new perspectives on the field of human resource and environmental management and offers strategic guidance and management insights for green management practices and organizational culture building.